Applications and Practices of Big Data for Development - Adusumalli, Harshini Priya; Pasupuleti, Mahesh Babu (Asian Business Review, 2017)
Daily, vast volumes of public data are generated due to the expansion of social media sites, digital computing devices, and Internet connectivity. Effective data analysis techniques/algorithms can provide near real-time knowledge regarding emerging patterns and early warning in case of an emergency (such as the outbreak of a viral disease). These data can also disclose several helpful indicators of socioeconomic and political events that can assist formulate effective public policy. This study examines the use of big data analytics for human development. As big data technology matures, it will be possible to use it for development purposes, such as addressing humanitarian crises or violent conflicts. The large-scale use of big data for development is fraught with obstacles due to its huge quantity, rapid change, and diversity. The most urgent challenges are effective data collection and exchange, providing context (e.g., geolocation and time), and ensuring data accuracy and privacy. This study reviews existing big data for development studies to assess the impact of big data on society’s development. We examine major efforts while also highlighting obstacles and unresolved issues.